Studies in marine quinone chemistry - Sunassee, Suthananda Naidu (Rhodes University, Faculty of Science, Department of Chemistry, 2011)
This thesis is divided into two parts and the rationale of the research conducted is based on the cytotoxicity of the prenylated quinones 1.24-1.29, isolated from the South African nudibranch Leminda millecra, against oesophageal cancer cells. The first part (Chapters 2 and 3) of the thesis initially documents the distribution of cytotoxic and antioxidant prenylated quinones and hydroquinones in the marine environment. We have been able to show, for the first time, that these compounds can be divided into eight structural classes closely related to their phyletic distribution. Secondly, we attempted to synthesize the two marine natural products 1.24 and 1.26 in an effort to contribute to an ongoing collaborative search with the Division of Medical Biochemistry at the University of Cape Town for new compounds with anti-oesophageal cancer activity. Accordingly, we followed the published synthetic procedure for 1.26 and, although we were unable to reproduce the reported results, we have generated five new prenylated quinone analogues 3.53-3.55, 3.63 and 3.71, which are a potentially viable addition to our ongoing structure-activity relationship (SAR) studies. Moreover, we embarked on a 7Li NMR mechanistic study for the synthesis of 3.2 from 3.1 which rewarded us with an improved and reproducible methodology for this crucial reaction that is detailed in Chapter 3. The second part of this
Keywords: Quinone; Marine natural products; Marine invertebrates; Marine pharmacology; Cancer -- Treatment